Phytochemical and glucose lowering potential of seaweed Eucheuma denticulatum (N.L.Burman) F.S. Collins & A.B. Hervey in vitro - R.M.T. Balasubramaniam, B. Vimala (2017)
Type 2 Diabetes Mellitus (T2DM) represents a serious global epidemic of the 21st century as reported by World Health Organisation (WHO). T2DM causes its own direct adverse effects as well as predisposes patients to the development of other chronic metabolic diseases such cardiovascular complications which lead to premature mortality. Thus, continuous search for remedies with minimum side effects were paramount. Scores of studies have demonstrated the health benefits derived from eating seaweed which promotes seaweed as a nutritional foodstuff. Moreover, research is advancing into using marine macroalgae also known as seaweed for production of novel foods and nutraceuticals. Modulating digestion with natural compounds has been shown to be a fruitful approach to the treatment of diabetes. The objectives of this study were to assess Malaysian seaweed species for their potential to regulate postprandial hyperglycaemia which is a pivotal feature of T2DM. Three species of Malaysian edible seaweed (Eucheuma denticulatum, Sargassum polycystum and Caulerpa lentillifera) found in coastal area of Sabah were selected and subjected to evaluation of their anti-diabetic potential in vitro in terms of their inhibition towards digestive enzymes that involve in hydrolysis of dietary carbohydrates (α-amylase and α-glucosidase). The seaweed were further subjected to other analyses related to glucose lowering properties such as antioxidant capacity, anti-inflammatory, adipogenesis, lipase enzyme inhibition and glucose uptake activities. Initially, the seaweed were screened and characterized for the presence of natural functional bioactive compounds which can be related to its health benefits. Following that, dinitrosalicylic acid assay was adapted in microplate to assess the inhibition of α-amylase activity while colorimetry method for α-glucosidase inhibition assay. Antioxidant capacity was evaluated for their free radical-scavenging capacity using 1, 1-diphenyl-2- pricrylhydrazyl (DPPH) assay and oxygen radical absorbance capacity (ORAC). The anti-inflammatory potential and cytotoxic effects of the seaweed samples were evaluated by the inhibitory activity of nitric oxide (NO), interleukin-6 (IL-6), interleukin-1 (IL-1), tumor necrosis factor-alpha (TNF-α), and monocyte chemoattractant protein-1 (MCP-1) on interferon-gamma/ lipopolysaccharide (IFN- γ/LPS) stimulated murine macrophage cell line (RAW 264.7) and adipocytes (3T3-L1) using Griess reaction, immunoassays and MTS assay. Adipogenesis and glucose uptake in 3T3-L1 were measured using commercial kits while lipase assay was measured by turbidimetric method. HPTLC, UHPLC and LC-MS/MS methods were established and validated for the quantitative determination of the identified compounds. The ethanolic extracts of the three species of seaweed showed the presence of carotenoids and the most notable being fucoxanthin, lutein, zeaxanthin, astaxanthin, canthaxanthin, β- cryptoxanthin, β-carotene and fatty acids such as palmitoleic acid (PA), docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). Fucoxanthin was the major carotenoid detected in the brown seaweed (S. polycystum) (2,740 mg/ 100 g DW). In the case of red seaweed (E. denticulatum), lutein (88 mg/ 100 g DW) and zeaxanthin (21 mg/ 100 g DW) were the major carotenoids, apart from small amount of fucoxanthin, while for the green seaweed (C. lentillifera), β-carotene (20 mg/ 100 g DW) and canthaxanthin (15 mg/ 100 g DW) were detected as major carotenoids. The method exhibited (a) linear calibration curves (R²>0.97), (b) satisfactory recoveries for most of the pigments (between 74 and 104%), and (d) low detection (from 0.001 to 0.01 ng/μl) and quantification limits (from 0.004 to 0.02 ng/μl) (LOD and LOQ, respectively). Ethanolic and methanolic extracts from the studied seaweed were found to display inhibitory effects against α-amylase (11-67%; n=3), but have no effect on α- glucosidase activity in vitro. Amongst the 3 genera, E. denticulatum ethanolic extract was found to be most effective in vitro inhibitors of α-amylase with IC50 of 0.14 mg/ml. Thus, this seaweed was selected for further solvent fractionation and bioactivity assays. Among the five investigated fractions (hexane, ethyl acetate, acetone, butanol and water), the hexane, ethyl acetate and acetone fractions exhibited good inhibition with a mean of 42%. The brown seaweed, S. polycystum displayed the highest DPPH radical scavenging and TPC (20%; 400 mg GAE/ 100 g respectively) whilst for ORAC analysis, E. denticulatum exhibited the highest activity at 112,762 μmol TE/ 100 g. E. denticulatum ethanol extract and fractions (1–100 μg/ml), also exhibited antiinflammatory activity without showing any cytotoxic effect to RAW 264.7 cells. The crude and fractions seem to inhibit adipogenesis and enhances glucose uptake in the 3T3-L1 cell model while ethanolic extract showed the highest lipase enzyme inhibitory (83%) compared to other sample preparation. The presence of fatty acids such as PA and EPA, antioxidant compounds such as polyphenols and carotenoids may probably contributed to the glucose lowering efficacy of these seaweed. In conclusion, this study demonstrated that E. denticulatum was able to exert bioactive actions such as antidiabetic, antioxidant, immune modulating and anti-obesity properties in vitro which suggesting its potential source as functional ingredient that can be further exploited to generate new valuable products for various commercial applications.